Morphology-dependent photoresponsive behaviors of a self-assembled system based on a single cyanostilbene derivative. Issue 31 (29th July 2022) - Zhang, Yangdaiyi; Ding, Zeyang; Ma, Yao; Jiang, Shimei
Abstract : Under blue light irradiation, the freshly prepared assemblies of nanoparticles lead to a [2+2] cycloaddition reaction, while the Z / E isomerization reaction occurs in the aged assemblies of microbelts. Abstract : In recent years, photoresponsive supramolecular self-assemblies have shown great potential in various fields. However, it is still a great challenge to integrate and control multiple photoresponsive behaviors in a self-assembled system. Herein, we design a novel cyanostilbene-based molecule VOE. In the aggregated state, it has different photoresponsive behaviors under different morphologies. When VOE molecules are dispersed in a 70% H2 O/THF mixture, two different assembly morphologies are obtained as the aging time changes. One is weakly emissive nanoparticles with amorphous packing arrangements, and the other is highly emissive microbelts with well-ordered stacking modes. When they are irradiated with blue light (420 nm), the disordered assembly structure of nanoparticles leads to a [2+2] cycloaddition reaction, while a Z / E isomerization reaction occurs in ordered packed microbelts. Therefore, we can use a self-assembled system to generate two different morphologies, enabling completely different emissions and photoresponsive behaviors.